Are Team Building Interventions Still Relevant? - Luqman Tifa Perwira; I Gde Dhika Widarnandana (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
Team building intervention is one form of intervention that is very popular in the world of organizational development practice. But unfortunately, empirically reported results often show inconsistency. This is because team building does not yet have a widely agreed theoretical construct. The inconsistency of the theoretical constructs that underlie the preparation of the modules used makes it difficult for researchers to evaluate the effectiveness of this intervention. This article attempts to offer a theoretical study of the formulation of team building and team training based on previously written articles. The formulation of the development intervention team described in this article is expected to be the theoretical basis for team development interventions in the next practical realm so that they can be more accountable in terms of concepts and methods to be able to provide more consistent results. Furthermore, it is necessary to prove empirically whether this formulation can be proven to improve various components of the team effectiveness indicators in field studies. Intervensi team building merupakan salah satu bentuk intervensi yang sangat popular dalam dunia praktek pengembangan organsasi. Namun sayangnya, secara empiris hasil yang dilaporkan kerap menunjukkan ketidakkonsistenan. Hal tersebut disebabkan team building belum memiliki konstruk teoritik yang disepakati secara meluas. Ketidakkonsistenan konstruk teoritik yang melandasi penyusunan modul yang digunakan menyebabkan sulit bagi peneliti untuk mengevaluasi efektivitas intervensi ini. Artikel ini berusaha untuk menawarkan studi teoritis mengenai rumusan team building dan team training yang didasarkan pada artikel-artikel yang telah dituliskan sebelumnya. Rumusan team development intervention yang dipaparkan dalam artikel ini diharapkan dapat menjadi dasar teoritik bagi intervensi-intervensi pengembangan tim di ranah praktis berikutnya agar dapat lebih dipertanggungjawabkan secara konsep maupun dan metode sehingga mampu memberikan hasil yang lebih konsisten. Selanjutnya, perlu pembuktian secara empiris apakah rumusan ini dapat terbukti meningkatkan berbagai komponen indikator efektivitas tim dalam studi lapangan.